Zaznavanje nevarnosti plačilne nesposobnosti - Juričič, Denis (Naše gospodarstvo, 2006)
A company's financial operations include providing and managing financial means and their resources, and allocating the resources of financial means in order to provide adequate conditions for economic activity. A company has to be liquid and solvent and it has to have adequate capital at its disposal. The purpose of this article is to analyse the necessary activities of a company concerning financial operations, and to analyse possible approaches to detecting the dangers of illiquidity and insolvency.
Keywords: podjetja; finančno poslovanje; plačilna sposobnost; likvidnost; solventnost; zadolženost